IMPROVING STUDENTS’ CONCENTRATION AND LEARNING OUTCOMES THROUGH PROJECT-BASED LEARNING ASSISTED BY GAMES AS THE METHOD - Vika Mutiara Ghozelin; Agnes Herlina Dwi Hadiyanti; Yohanes Bruri Kriswanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper is based on the students’ low concentration and learning outcomes. The purpose of the research is to increase the students’ concentration and learning outcomes through the project-based learning model assisted by the game method. The type of research is classroom action research. The research subjects were students at class 4A of SD Kanisius Demangan Baru 1. The research object was the improvement of students’ concentration and learning outcomes through the project-based learning model assisted by the game method. Data collection techniques were obtained through observation, interviews, and tests. The data analysis techniques used were quantitative and qualitative. The research results indicate that the percentage of students' learning concentration before applying the action was still in the low percentage (58.33%), after conducting the first cycle increased to the moderate category level (69.44%), and after conducting the second cycle increased to the excellent category (90.27). The average mastery level of students’ learning outcomes of students before applying the action was still in the low category (57.27). After conducting the first cycle, the student’s learning outcomes increased to the medium category (67.72), and after applying the second cycle increased to the high category (84.09). Thus, students’ learning concentration influences their learning outcomes. It is because if students can focus their attention so they can optimize their ability to respond to the lesson that they learned, so their learning outcomes also increase.